HEALTH-FIELD CADRES EMPOWERMENT FOR PREVENTION AND EARLY DETECTION OF COMMUNITY MENTAL HEALTH PROBLEMS - Bahari, Kissa; Widodo, Dyah; Soebagijono, Soebagijono (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2025)
Currently, the number of mental health problems in Indonesia is more and more increased. Health-field cadres have important roles in taking part in preventing and early detecting community mental health problems. This community service aimed to improve the ability of health-field cadres in preventing and early detecting community mental health problems in the Bantur Primary Health Center, Malang. The results showed that the ability of health-field cadres before training program is low; conversely, after the training program, there was a significant improvement of knowledge and skills in preventing and detecting community mental health problems. We suggest Bantur Primary Health Center make planning a training program for other health-field cadres; so, the number of health-field cadres who can prevent and early detect of community mental health problems will be higher. Innovation in developing android-based applications for early detection of community mental health problems also need to start to address distance and infrastructure barriers.